The First Described Nymphs and Detailed Imagoes of the Species Thalerosphyrus cingulatus Navás Revealing a New Mayfly Genus from Eastern China (Ephemeroptera: Heptageniidae, Ecdyonurinae) - Zhiming Lei (MDPI AG, 2021)
The nymph and detailed imaginal morphology of the Chinese mayfly Thalerosphyrus cingulatus have not been reported since it was named by Navás in 1933. Here based on newly collected nymphal and associated imaginal materials of this species from eastern China, we find both nymphs and adults have several extraordinary characters. In adults, forewings have less crossveins in costal and subcostal sections, others crossveins arranged into five regular rows; tibiae and tarsi of midlegs and hindlegs subequal in length; male compound eyes widely separated and penes simple and fused. The nymphs have greatly extended lateral pronotum, round supracoxal spurs and extended dorsal lamellae of gills, especially those of the gills VII; maxillae have two independent distal dentisetae. These combined characters represent a new generic taxon. Therefore, Regulaneuria Zhou, gen. nov. is established here to include the species Regulaneuria cingulata (Navás, 1933) comb. nov. The forewing venation of the species R. cingulata is unique in the family Heptageniidae but similar to some counterparts of Leptophlebiidae and Baetidae.